The Francis effect : a radical pope's challenge to the American Catholic Church - Gehring, John, 1974- (Rowman and Littlefield, 2015)
This book explores how a church once known as a force for social justice became known for a few key wedge issues, then looks at the opportunities for change in the "age of Francis." The first non-European pope in more than a millennium, Pope Francis is shaking up a church that has been mired in scandal and demoralized by devastating headlines